The Effect of Promotion on Mobile Phone Purchase Decisions at CV Tricomsel Gunungsitoli-Nias - Zebua, Putra Bakti; Telaumbanua, Aferiaman; Mendrofa, Yupiter; Bate'e, Maria Magdalena (ProBisnis : Jurnal Manajemen, 2025)
This study examines the influence of promotion on consumer purchasing decisions of mobile phone products at CV. Tricomsel Gunungsitoli-Nias. Promotion is considered a crucial element in the marketing mix that shapes consumer behavior and purchasing patterns. A quantitative research approach was employed, using primary data collected through questionnaires distributed to 62 respondents selected via simple random sampling from a population of 160 consumers. The research instruments were tested for validity and reliability, and the data were analyzed using simple linear regression, t-test, and coefficient of determination (R²). The findings reveal that promotion has a positive and significant effect on purchasing decisions. The regression coefficient (B = 0.588) indicates a positive relationship, with a calculated t-value of 7.764, which exceeds the t-table value. Furthermore, the significance level (0.000) is below 0.05, confirming the strong effect of promotion on purchasing behavior. The R² value of 0.501 demonstrates that 50.1% of purchasing decisions are explained by promotional activities, while the remaining 49.9% are influenced by other factors not addressed in this study. These results highlight the importance of developing innovative promotional strategies to strengthen competitiveness in the mobile phone retail industry, particularly within the local market context of Gunungsitoli-Nias.